Training and psychosocial patterns during the early development of Portuguese national team athletes - Barreiros, A.; Côté, J.; Fonseca, A. M. (High Ability Studies, 2013)
This study explored the early development of expert athletes compared to a group of athletes that did not achieve an expert level of performance despite being involved in youth events with their national squads. In particular, the activities, training patterns, and psychosocial influences that characterized their paths in competitive sports were examined. Male and female participants (N = 42) from different sports were interviewed. Overall, athletes showed several commonalities. However, experts were selected to national squads later and also started thinking about investing in becoming elite athletes later. Non-experts revealed more parental pressure and less individual training with coaches.